THE REMOVAL EFFICIENCY OF ORGANIC LOADING, PHOSPHATES AND DETERGENTS IN WASTEWATER OF CAR WASH SERVICE BY CONSTRUCTED WETLAND SYSTEM - Theofilus Stm; Haryati Bawole Sutanto; Guruh Prihatmo (Universitas Medan Area, 2022)
The car wash wastewater has a proportion of detergent and it can cause considerable impacts to pollute the environment and health if they are not processed in well. SSVF CW is one of an alternative wastewater treatment, because it has the advantage such as wastewater flowing below the surface of the media so it reduces the smell of wastewater. The objective of this study was to determine the removal efficiency of reducing pollutants in the wastewater of treated car wash by Constructed Wetland and the influence of Chrysopogon zizanioides rhizosphere depth in supplying DO distribution. This experimental laboratory scale study used 2 PVC for reactor. Each pipe has 4 sampling points. The DO was measured from different depth, while the other parameters were from the effluent. The ratio of the media used was 1:3:2:4 from the top to the bottom. The SSVF CW system had high TSS removal efficiency of 94.74%, while the removal efficiency of COD, Detergent, and Phosphate was76.21%, 54.54%, 30.65%, respectively. DO distribution at a depth of 84 cm in both pipes increased even though the root zone was only 26.5 cm.